1994
DOI: 10.1021/ja00095a006
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the .alpha. versus .beta. Bond Cleavage in the Direct and Triplet-Sensitized Photolysis of Azoalkanes of the 2,3-Diazabicyclo[2.2.1]hept-2-ene Type

Abstract: On direct irradiation, the azoalkanes anti-hexahydro-1,4:5,8-dimethanophthalazines (Sa, 1,4-H; Sb, 1,4-Me;SC, 1,4-Ph) do not only give the expected housanes 6 through a C-N bond cleavage and subsequent denitrogenation but also yield, in the order Sa > Sb > 5c, the rearranged aziranes 7 through /3 C-C bond cleavage. The increased formation of the heterocycles 7 on triplet sensitization with benzophenone and the suppression of these rearrangement products by the triplet quenchers trans-piperylene and 1,3-cyclohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In summary, the triplet state of azoalkanes has until recently been highly elusive. With the recent observation [16][17][18] of phosphorescence from rigid DBH analogs, 2, and the present PAC studies, these species are now better characterized. Interesting questions remain nevertheless, such as the decay mode of flexible azoalkane triplets and the nature of the decomposing state, 3 Q.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In summary, the triplet state of azoalkanes has until recently been highly elusive. With the recent observation [16][17][18] of phosphorescence from rigid DBH analogs, 2, and the present PAC studies, these species are now better characterized. Interesting questions remain nevertheless, such as the decay mode of flexible azoalkane triplets and the nature of the decomposing state, 3 Q.…”
Section: Resultsmentioning
confidence: 87%
“…Recently, Adam and co-workers found that 2 intersystem crosses to a directly observable triplet whose lifetime is 0.65 μs . The contrast between 2 and other DBH's is striking; , for example, 3 does not intersystem cross to any appreciable extent, as judged from product ratios …”
Section: Introductionmentioning
confidence: 99%
“…700 ns in acetonitrile), long-lived azoalkane triplet states have remained elusive , until the recent detailed examination of the photochemistry of azoalkanes 1 revealed the existence of quite persistent azo triplets . The azoalkanes 1 (Scheme ) are unique in that spontaneous ISC to the triplet state prevails over the deactivation of singlet-excited states by either rapid nitrogen extrusion or fluorescence. ,, Direct photoexcitation of azoalkanes 1a and 1b affords not only the expected α C−N cleavage products, viz., the housanes 2 , but also the aziranes 3 derived from β C−C bond cleavage. From quenching experiments, the triplet quantum yields for the azoalkanes 1a and 1b have been estimated to be as high as 0.5. ,, In contrast, the bridgehead phenyl-substituted azoalkane 1d exhibits significantly lower ISC quantum yields (ca.…”
Section: Introductionmentioning
confidence: 99%
“…The azoalkanes 1 (Scheme ) are unique in that spontaneous ISC to the triplet state prevails over the deactivation of singlet-excited states by either rapid nitrogen extrusion or fluorescence. ,, Direct photoexcitation of azoalkanes 1a and 1b affords not only the expected α C−N cleavage products, viz., the housanes 2 , but also the aziranes 3 derived from β C−C bond cleavage. From quenching experiments, the triplet quantum yields for the azoalkanes 1a and 1b have been estimated to be as high as 0.5. ,, In contrast, the bridgehead phenyl-substituted azoalkane 1d exhibits significantly lower ISC quantum yields (ca. 0.10), since the benzylic radical stabilization favors nitrogen extrusion in the singlet manifold.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, cycloalkanones undergo either a Norrish type I (path a) [6][7][8][9] or a Norrish type II (path b) [6][7][8][10][11][12][13] reaction affording diradicals that, in the latter case, may recombine via the well-known Norrish-Yang reaction [6,7,[10][11][12][13]. Diradicals are also intermediates in photoextrusion reactions (path c) [6,7] where the photorelease of a stable molecule, such as CO (in cyclic ketones) [14][15][16], dinitrogen (in azoalkanes) [17][18][19][20] or SO 2 (in sulfones, path c) [21], is followed by the concomitant radical-radical coupling of the radical sites in the resulting diradical. Diradicals are also key intermediates in photo-Fries rearrangements of lactones and lactams as illustrated in Scheme 1, path d [6,7,22].…”
Section: Introductionmentioning
confidence: 99%